Maḥakk-i Khusrawī - Bayg, Mīrzā Khusraw, (Miras Maktoob, ISBN: 9789004365452., 2019)
When the founder of the Qajar dynasty of Iran, Āqā Muḥammad Khān Qājār (r. 1789-97), conquered the capital of Georgia Tiflis in 1795, two infant sons of the defeated king Heraclius II were captured. Of these, the eldest died on the way. The other, Khusraw Khān, the later Mīrzā Khusraw Bayg Gurjī (d. 1277/1860), was taken back to Tehran by the commander of the Persian forces, Ḥājjī Ibrāhīm, who treated him as if he were his own child, calling him Mīrzā. When Ḥājjī Ibrāhīm was executed in 1803 on the orders of Fatḥ ʿAlī Shāh (d. 1249/1834), Mīrzā Khusraw first lived with a family in Shiraz and then, in 1805, he was adopted by the childless Talpur ruler of Sind, Mīr Karam ʿAlī Khān (r. 1227-44/1812-28). It is there at the court in Hyderabad that he developed into a refined man of letters and where he compiled this poetical anthology, then only 27 years old.